IMPLEMENTASI KEBIJAKAN PEMBERDAYAAN MASYARAKAT KELUARGA MISKIN DI KOTA PONTIANAK - Martoyo - Martoyo (Jurnal Sosial Humaniora, 2020)
The focus of this research is the implementation of the policy of poverty communities empowering of family welfare income increasing group (UPPKS) at Pontianak City. These study were answered the question of how was implementation of poverty communities empowering policy UPPKS group at Pontianak City were implemented. There were a correlation between the unsuccessful of poverty communities empowering policy implementation to the organizational activites, interpretation, and application of policy implementation.These study used a qualitative descriptive method with its main instrument were the researcher itself, where collecting process, analysis, interpretation, and data verification of any primary and secondary data information which have been obtained through in-depth interviews, observation, and documentation of background events setting, situation, and empirical condition of poverty communities empowering policy UPPKS group at Pontianak City which were expressed objectively.The study found that implementation of poverty communities empowering policy UPPKS group has not succesful yet to achieve, due to unoptimalized capacity of the implementing authorities on to implemented their organizational activities, interpretation, and application. The most crucial thing on to implementation of poverty communities empowering policy UPPKS  group was commitment and implementor’s allignment from leader to implementor level to implement the policy in accordance with policy objectives.Believed that to the existency of comitment and implementor’s allignment, the implementation of poverty communities empowering policy UPPKS  group will be effective according to policy’s goals.